The Digital Divide in the University: The Appropriation of ICT in Higher Education Students from Bogota, Colombia - Berrio-Zapata, Cristian [UNESP]; Rojas, Hernando (Grupo Comunicar, 2014)
The growth and integration of ICTs in the global economy have created conditions that profoundly affect our society, dividing communities between those who effectively appropriate these resources and those who do not, what is called the digital divide. This exploratory study seeks to propose and validate ways of assessing this phenomenon in higher education, from the construction of a model and a comprehensive methodology that value contextual conditions, in addition to measuring access factors and motivation for use, that have been employed in previous research. To obtain indications about the behavior of this phenomenon, we developed research with students from three universities in Bogota, administering 566 surveys in four phases that would test the variables proposed in the model. The results show that the variables of the model link causally, with the strongest relations between education, attitude towards ICTs and ICT application. Although students have good access to ICTs and high levels of education, no strong relationship was found in regards to perceived impact on production. This may be explained by a superficial appropriation of ICT, due to a context that is alien to its conditions of origin (industrialism, innovation), poor quality of education and economies not centered around R&D.
Keywords: Digital divide; graduate education; technology appropriation; literacy; discourse; technological education; critical analysis